2019
DOI: 10.1007/s10734-019-00360-0
|View full text |Cite
|
Sign up to set email alerts
|

Staff views on commercial contract cheating in higher education: a survey study in Australia and the UK

Abstract: Contract cheating is, potentially, a serious threat to the quality of higher education around the world. Prior research has focused on student perspectives and the companies themselves, but the staff view is poorly understood, despite staff being a major stakeholder with considerable influence over strategies designed to address contract cheating. We surveyed staff in Australia and the UK about their views on contract cheating. We asked staff to estimate the extent of contract cheating, how much it cost studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The university often rule in favour of the student on grounds of 'lack of evidence' though it is clear to everyone that the essay has been bought. This finding is supported by Awdry and Newton [15], who found similar lenient outcome in their study. But why are some universities reluctant to adopt a more rigorous approach like YN's university has done?…”
Section: Universities' Nonchalancesupporting
confidence: 84%
See 1 more Smart Citation
“…The university often rule in favour of the student on grounds of 'lack of evidence' though it is clear to everyone that the essay has been bought. This finding is supported by Awdry and Newton [15], who found similar lenient outcome in their study. But why are some universities reluctant to adopt a more rigorous approach like YN's university has done?…”
Section: Universities' Nonchalancesupporting
confidence: 84%
“…Therefore, there is still a gap here that needs to be filled. Other researchers like Awdry and Newton [15], have surveyed staff views on commercial contract cheating in higher education in Australia and the UK. They reported that a large proportion of staff in these two countries admitted having experienced contract cheating with students at their universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The questions in the interview were developed to gain participants' perceptions of contract cheating in the courses that they teach within their institutes. The questions were adapted from similar studies conducted by Ali and Alhassan (2021) who conducted a qualitative study among higher education institutes in Oman, a culturally similar country to Kuwait; and Awdry and Newton (2019) who surveyed staff views in Australian and British universities via a questionnaire. This study has expanded on these previous studies by including questions assessing faculty members' viewpoints regarding the impact of COVID-19 on contract cheating.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, researchers' focus has shifted in two directions worldwide. Firstly, the studies clearly concentrate on written works, where it is not only possible to detect potential plagiarism automatically (Do Ba et al, 2016 ; Foltýnek et al, 2019 ; Lancaster & Clarke, 2012 ) but also evaluate to what extent the work as a whole has been prepared by someone else with the consent of the original author ( contract cheating, ghostwriting, essay mills ) (Awdry & Newton, 2019 ; Bielska, 2015 ; cf. the opinion on the role of writing centres in Clarke, 1999 ).…”
Section: Copying In Higher Educationmentioning
confidence: 99%